2020
DOI: 10.1177/0954405420911298
|View full text |Cite
|
Sign up to set email alerts
|

Tool tip cutting specific energy prediction model and the influence of machining parameters and tool wear in milling

Abstract: Most of the existing energy-consumption models of machine tools are related to specific machine components and hence cannot be applied to other machine tools with different specifications. In order to help operators optimize machining parameters for improving energy efficiency, the tool tip cutting specific energy prediction model based on machining parameters and tool wear in milling is developed, which is independent of the standby power of machine tools and the spindle no-load power. Then, the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…where: k and e-the number of parameters considered and approximate error; b i , b ii , and b ij -the regression coefficients. The total specific energy (SEC) is defined as the ratio of the total energy consumption to the material removal volume and computed as 27,28 :…”
Section: Optimization Targetsmentioning
confidence: 99%
“…where: k and e-the number of parameters considered and approximate error; b i , b ii , and b ij -the regression coefficients. The total specific energy (SEC) is defined as the ratio of the total energy consumption to the material removal volume and computed as 27,28 :…”
Section: Optimization Targetsmentioning
confidence: 99%
“…The results of this experiment showed that the specific cutting energy ranged from 4.1 to 8.6 W s/mm 3 , which is comparable with earlier studies shown in Table 5. [11][12][13][14][15][16] Recent work by Guo et al 17 was not focused on similar workpiece material class. This increasing body of evidence at tool wear driving increase in specific energy needs to be considering in modelling so that machining optimisation is more realistic and does not assume sharp tools.…”
Section: Effect Of Tool Wear On Cutting Powermentioning
confidence: 99%
“…Though these models can accurately predict energy consumption, they fail to consider the influence of factors other than cutting parameters on energy consumption, such as tool parameters or tool wear. Based on this consideration, Zhao et al [8] analyzed the effect of tool wear on machine tool energy consumption in 45# steel semi-finishing milling, and developed a machine power model with MRR and tool wear as the inputs. The study showed that cutting energy consumption can be reduced by monitoring and controlling tool wear.…”
Section: Introductionmentioning
confidence: 99%